2016
DOI: 10.1101/052290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the evolutionary origins of equity

Abstract: Equity, defined as reward according to contribution, is considered a central aspect of human fairness in both philosophical debates and scientific research. Despite large amounts of research on the evolutionary origins of fairness, the evolutionary rationale behind equity is still unknown. Here, we investigate how equity can be understood in the context of the cooperative environment in which humans evolved. We model a population of individuals who cooperate to produce and divide a resource, and choose their c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Anthropological observations show that defection in traditional societies is mostly met with a passive abandonment rather than with more defection in return (see Baumard et al, for a review). Also, several theoretical studies have shown that partner choice can account for the evolution of other important properties of human cooperation, such as the fact that its benefits are often shared in proportion to everyone's respective effort in producing them (André & Baumard, , ; Chiang, ; Debove, André, et al, ; Debove Baumard, & André, , ; Takesue, ).…”
Section: Discussionmentioning
confidence: 99%
“…Anthropological observations show that defection in traditional societies is mostly met with a passive abandonment rather than with more defection in return (see Baumard et al, for a review). Also, several theoretical studies have shown that partner choice can account for the evolution of other important properties of human cooperation, such as the fact that its benefits are often shared in proportion to everyone's respective effort in producing them (André & Baumard, , ; Chiang, ; Debove, André, et al, ; Debove Baumard, & André, , ; Takesue, ).…”
Section: Discussionmentioning
confidence: 99%
“…Even if there exist 'systematic asymmetries of strength' between individuals, equal divisions can evolve in a broad range of circumstances ([2015], p. 562). Another newer model shows that if individuals make unequal investments, selection favours proportional, equitable divisions rather than just equal ones (Debove et al [2017]). These elaborations still leave us with many aspects of the models that could be questioned for their ecological validity (such as the assumption that choosing and/or switching partners is cheap: a key assumption that is needed to guarantee equitable outcomes).…”
Section: Markets Without Market Dynamics?mentioning
confidence: 99%
“….] the result of this bargaining is the existence of a genuine sense of fairness which 'automatically' makes humans prefer equitable strategies' (Debove et al [2017], p. 11). Baumard et al explicitly contrast these ultimate biological markets where selection favours automatic, inflexible dispositions with proximate biological markets where individuals flexibly adjust the price they pay to changes in supply and demand (as in the examples from Section 2).…”
Section: Markets and Evolutionary Continuitymentioning
confidence: 99%
“…However, it is unclear to us to what extent these processes are really distinct from one another. In their target article, B&P mention the importance of fairness several times and describe it as the result of partner choice: When individuals are in competition with one another to be chosen as cooperative partners, they have no choice but to share the benefits of cooperation in a fair way (Baumard et al 2013a;Debove et al 2017). The goal of fairness mechanisms is to help individuals solve the following question: "Did I get as many benefits as others from the interaction given my effort, my talent, or my opportunity costs?"…”
Section: Fairness More Than Any Other Cognitive Mechanism Is What Ementioning
confidence: 99%